Pengembangan Komik Edukasi Sebagai Media Untuk Meningkatkan Pemahaman Bahaya Merokok Siswa di SMK Negeri 10 Makassar - Galigo, Andi Agung Putra; Pandang, Abdullah; Mansyur, Ahmad Yasser (Guidance : Jurnal Bimbingan dan Konseling, 2024)
This study aims to determine; (i) a description of the need for educational comic media as a medium to prevent smoking behavior of students at SMK Negeri 10 Makassar. (ii) the acceptability of educational comic media as a medium to prevent smoking behavior of students at SMK Negeri 10 Makassar. The subjects in this study were grade X students at SMK Negeri 10 Makassar. This study used data collection techniques through interviews and questionnaires. The data analysis used quantitative and qualitative data analysis. The results of the study showed that: (i) a description of the need for developing comic media to prevent smoking behavior of students at SMK Negeri 10 Makassar that the high level of student ignorance of the impacts caused by cigarettes so that some students smoke. (ii) a description of the results of the acceptability test of educational comic media that educational comic media is feasible and can be used to prevent smoking behavior of students at SMK Negeri 10 Makassar, namely with a total score of 63, with a percentage of 98.45% with very good qualifications.